A frequent SNP in TRIM5α strongly enhances the innate immune response against LINE-1 elements - Lagisquet, Justine; Conrad, Marcus; Wittmann, Sabine; Volkmann, Bianca; Weissinger, Hannah; Sticht, Heinrich; Gramberg, Thomas (Frontiers in Immunology, 2023)
The intracellular restriction factor TRIM5α inhibits endogenous LINE-1 retroelements. It induces innate immune signaling cascades upon sensing of cytoplasmic LINE-1 complexes, thereby underlining its importance for protecting the human genome from harmful retrotransposition events. Here, we show that a frequent SNP within the RING domain of TRIM5α, resulting in the variant H43Y, blocks LINE-1 retrotransposition with higher efficiency compared to TRIM5α WT. Upon sensing of LINE-1 complexes in the cytoplasm, TRIM5α H43Y activates both NF-κB and AP-1 signaling pathways more potently than TRIM5α WT, triggering a strong block of the LINE-1 promoter. Interestingly, the H43Y allele lost its antiviral function suggesting that its enhanced activity against endogenous LINE-1 elements is the driving force behind its maintenance within the population. Thus, our study suggests that the H43Y variant of the restriction factor and sensor TRIM5α persists within the human population since it preserves our genome from uncontrolled LINE-1 retrotransposition with higher efficiency.